Bengkel Sastra untuk Penguatan Literasi Budaya dan Kewargaan di SMKS YPK Merauke - Sri Winarsih; Margaretha F. Narahawarin; Suci Rahmadani (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Based on the problems experienced by SMKS YPK Merauke, namely the low ability and interest in reading and writing of students and the existence of friendship patterns based on ethnicity and class so that conflicts between friends often occur, the Literature Workshop program to Strengthen Cultural and Citizenship Literacy was held. Literature workshops are a solution to the problem of the low ability and interest in reading and writing of students, while Cultural and Citizenship Literacy are to overcome problems where there are still classifications and disputes between students. Methods in the implementation of Literature Workshop are; 1) Open Workshop; the introduction stage of the Literary Workshop Program and the Cultural and Citizenship Literacy Movement, 2) Disassembling; the practice stage of reading and writing literary works with cultural themes, and 3) Patchy; the mentoring stage through consultation on student work and evaluation of Program Sustainability. The result of this activity; 1) Increasing students' understanding of the world of literature and cultural literacy and citizenship as measured through tests at the end of Open Workshop activities, 2) Increasing students' competence in reading and writing as measured through practice making short stories with the theme of Papuan folklore, and 3) Increasing social skills and mutual respect for cultural differences as measured by assignments using the case study method, 4) Drafts of folklore collection by students, 5) Drafts of Cultural and Citizenship literacy programs by teachers.